Evaluation of 3D Photogrammetry Tools for Applications in the Scanning Electron Microscope - Gannon, Edward Byron (Trinity College Dublin. School of Physics. Discipline of Physics, 2023)
3D models find application in a range of materials science areas, from fractography and failure studies to 3D printed metal topology. Atomic force microscopy (AFM) is commonly used for measuring surface topology, though this is limited to relatively flat surfaces and by tip geometry. However, 3D data can be obtained from scanning electron microscope (SEM) images via quadrant detectors (“shape from shading”), stereo pair reconstructions or photogrammetric datasets. Photogrammetry constructs 3D models from several 2D images at different viewpoints through the use of a number of mathematical algorithms to extract the scene’s geometry. With the reconstruction only requiring 2 or more 2D images, standard SEM imaging can be used in place of digital photography, and without requiring specialised hardware. The widespread popularity of photogrammetry has created an upsurge in reconstruction software, both commercial and open source, whose rapid advancements can be leveraged for SEM applications. Photogrammetry, however, can be a time consuming and expensive process, depending on the sample being imaged and the software used for model reconstruction. We demonstrate an efficient method for ‘microscopy for photogrammetry’, developing a framework for selecting imaging parameters to ensure a satisfactory photogrammetric data set is acquired. This results in a practical and accessible procedure for reconstructing 3D microscale structures using open-source photogrammetry software in the SEM.
APPROVED
Keywords: Instrument development; Scanning electron microscopy; Photogrammetry; 3D imaging